Federico A. Daus, El desarrollo argentino, Buenos Aires, Eudeba, 1969, 110 p. - Richard, Rodolfo Alberto (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Geografía, 1970)

(untitled)
Fil: Richard, Rodolfo Alberto.